The Development of WODA’S (Word of Our Daily) Book on Improving Students Vocabulary Mastery - Ilvi Ainun Nisa; Muh Shofiyuddin (Journal of Education Research, 2023)
The purpose of this study was to develop a learning media that can be used to improve  vocabulary acquisition in middle school students. The medium developed was his WODA book, which describes media developments in  vocabulary instruction for middle school students. This study was conducted in an Islamic secondary school in Jepara with research and development as the research design. This learning media also includes interactive games and colorful pictures  to teach vocabulary to middle school students. The research design was research and development using the ADDIE model, which consists of 's analysis, design, development, implementation, and evaluation. The researchers have completed this study to the implementation stage. Data was collected through verification results by  learning media experts. In the media expert's results, the  score rate in the effective category, and the lecture material expert reported that his was effective. According to the result analysis, WODA game book, with its highly interactive images and color display, can be effectively used as  vocabulary learning media and has the potential to attract  students to the learning process in middle school, but there is still a need It includes several points that I think are important. In particular, we will improve  the content  and variety of the game. Based on the results of the analysis, we found that it is possible to use Woda's playbook for teaching and learning English.